Women as Breadwinners: A Butlerian Feminist Perspective on Female Agricultural Labor - Shahab, Firdaus binti; Ulya, Zakiyatul (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
This study explores the phenomenon of eleven women in Besuk Kidul Village, Besuk District, Probolinggo Regency, who have become the primary breadwinners in their families. Among agricultural laborers, this role reversal emerges from men’s limited employment opportunities, health constraints, and inability to fulfill household needs. Drawing on Judith Butler’s feminist framework, which views gender as performative, fluid, and socially constructed, the study interprets this shift as a form of resistance to traditional gender norms and an affirmation of women’s agency within patriarchal structures. Using a qualitative field research design, data were obtained through observation and in-depth interviews and analyzed descriptively with reference to Butlerian concepts of gender performativity, deconstruction of gender fluidity, and female subjectivity. The findings highlight three key aspects of women’s dominance: their central role in organizing household labor, their authority in family decision-making—including daily needs, children’s education, and health care—and their independent management of household finances through savings and arisan (rotating credit associations). These results demonstrate how women in rural contexts negotiate and redefine gender roles through economic agency.